A zebrafish model of congenital nephrotic syndrome of the Finnish type - Lee, Mi-Sun; Devi, Sulochana; He, John Cijiang; Zhou, Weibin (Frontiers in Cell and Developmental Biology, 2022)
Nephrotic syndrome (NS) is a disease characterized by proteinuria and subsequent hypoalbuminemia, hyperlipidemia and edema due to the defective renal glomerular filtration barrier (GFB). NEPHRIN, encoded by the human NPHS1 gene, is a podocyte protein essential for normal GFB. Mutations of NPHS1 cause congenital nephrotic syndrome of the Finnish type (CNF), an autosomal recessive disease accounting for about 50% of congenital NS cases. Here, we report a zebrafish model of CNF generated by using CRISPR/Cas9 to introduce deletions in the zebrafish nphs1 gene. These mutants completely lack nephrin protein expression in podocytes and develop progressive peri-orbital and whole-body edema after 5 days post fertilization and lethality within two weeks of age. Ultra-structurally, loss of nephrin results in absence of slit-diaphragms and progressive foot process effacement in zebrafish pronephric glomeruli, similar to the pathological changes in human CNF patients. Using a reporter line Tg(l-fabp:VDBP-GFP) expressing GFP-tagged vitamin-D-binding protein in the blood plasma, we observed a reduction of intravascular GFP fluorescence in the nphs1 mutants, a hypoalbuminemia-like phenotype. Therefore, we have demonstrated that the nphs1 mutant zebrafish recapitulate the human NS phenotypes and provide a novel and relevant animal model useful for screening therapeutical agents for this disease.